1881 N.Y. Laws 102, tit. 12, § 409 - (:unkn) unknown (General Publisher, 1881)
Prohibited the manufacture, sale, giving, or disposing of any instrument or weapon usually known as a slungshot, billy, sand-club, or metal knuckles and prohibited the carrying any slungshot or similar weapon. Violators guilty of a misdemeanor.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS